1992
DOI: 10.1095/biolreprod46.6.1127
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Testoserone on Serum Gonadotropins of Castrated Rats Kept under Different Lighting Conditions1

Abstract: Testosterone feedback sensitivity was measured as the ability of testosterone propionate to decrease serum LH and FSH of long-term castrated (4 wk) rats under four different lighting conditions: periodic light (12L:12D), constant light (LL), constant darkness (DD), and dim night illumination (1 lx) with a 12L:12D photoperiod. Rats were exposed to the different lighting conditions for 1 wk, during which they received daily testosterone propionate (125 micrograms or 250 micrograms s.c.). At the end of the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Certainly, serum levels of both LH and FSH were significantly decreased in rats from the TP group when compared to those of the DW group. TP has been reported to show an androgenic effect to suppress the secretion of FSH and LH from the pituitary and GnRH from the hypothalamus (Porkka-Heiskanen et al, 1992). Body weights of the adult cyclic rats in all BS groups did not significantly differ from those in the DW group, whereas the body weight of rats in the TP group were significantly higher, in agreement with the fact that androgenic substances increase food intake and that TP is a potent anabolic steroid (Earley and Leonard, 1979).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Certainly, serum levels of both LH and FSH were significantly decreased in rats from the TP group when compared to those of the DW group. TP has been reported to show an androgenic effect to suppress the secretion of FSH and LH from the pituitary and GnRH from the hypothalamus (Porkka-Heiskanen et al, 1992). Body weights of the adult cyclic rats in all BS groups did not significantly differ from those in the DW group, whereas the body weight of rats in the TP group were significantly higher, in agreement with the fact that androgenic substances increase food intake and that TP is a potent anabolic steroid (Earley and Leonard, 1979).…”
Section: Discussionsupporting
confidence: 63%
“…That the ovariectomies were complete was supported by the increase in serum FSH and LH levels (Porkka-Heiskanen et al, 1992). No effect of Butea superba on serum FSH and LH levels in the ovariectomized rats was observed in the BS-10 group, but in the BS-50 and BS-250 groups the serum LH levels were increased after Butea superba treatment for 15 days.…”
Section: Discussionmentioning
confidence: 84%
“…This may be because the negative feedback effects between testosterone and LH and/or FSH were inhibited. It has been reported that the sensitivity of the negative feedback of testosterone is not influenced by lighting condition [22], but in the present experiment, this sensitivity appeared to be reduced as a result of the combination of constant darkness and the low-protein diet. However, further study is needed to determine the steroid feedback mechanism, analyzing for the dynamic state of LH, FsH, inhibin, and GnRH in gonadectomized rats kept under constant darkness and fed a low-protein diet.…”
Section: Discussioncontrasting
confidence: 67%
“…Indeed, after FSH and LH secretion from the pituitary gland is reduced (20), the endogenous testosterone secretion from Leydig cells should subsequently be reduced. Although the serum LH and FSH levels were decreased during the TP treatment, the extent of reduction of LH levels was greater than that of FSH levels, and only the serum FSH levels returned to pre-treatment values during the post-treatment period.…”
Section: Discussionmentioning
confidence: 99%